2012
DOI: 10.1038/nature11435
|View full text |Cite
|
Sign up to set email alerts
|

Androgenetic haploid embryonic stem cells produce live transgenic mice

Abstract: Haploids and double haploids are important resources for studying recessive traits and have large impacts on crop breeding, but natural haploids are rare in animals. Mammalian haploids are restricted to germline cells and are occasionally found in tumours with massive chromosome loss. Recent success in establishing haploid embryonic stem (ES) cells in medaka fish and mice raised the possibility of using engineered mammalian haploid cells in genetic studies. However, the availability and functional characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
206
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 155 publications
(217 citation statements)
references
References 29 publications
9
206
0
2
Order By: Relevance
“…Generation of gynogenetic bimaternal mice containing two sets of maternal genomes was achieved using non-growing oocytes with imprinting modifications [4]; however, the approach was technically challenging and impractical for further applications. Recently, we and others have derived mammalian androgenetic and parthenogenetic haploid embryonic stem cells (ahESCs and phESCs), and showed that ahESCs can replace gametes to produce offspring [5][6][7], which provided alternative resources for reproduction [6,7]. Here we report that after proper imprinting modifications, the mouse phESCs can efficiently produce viable fertile offspring upon intracytoplasmic injection into MII oocytes.…”
Section: Dear Editormentioning
confidence: 80%
“…Generation of gynogenetic bimaternal mice containing two sets of maternal genomes was achieved using non-growing oocytes with imprinting modifications [4]; however, the approach was technically challenging and impractical for further applications. Recently, we and others have derived mammalian androgenetic and parthenogenetic haploid embryonic stem cells (ahESCs and phESCs), and showed that ahESCs can replace gametes to produce offspring [5][6][7], which provided alternative resources for reproduction [6,7]. Here we report that after proper imprinting modifications, the mouse phESCs can efficiently produce viable fertile offspring upon intracytoplasmic injection into MII oocytes.…”
Section: Dear Editormentioning
confidence: 80%
“…Spermatozoa were released from the cauda epididymis with forceps compressing [50] and suspended in M2 medium. ICSI was then carried out as described previously [51][52][53] with some modifications. Briefly, 10 µl of sperm suspension was added to 1 ml M2 medium supplemented with 5 µg/ml of cytochalasin B, and 15-20 mature oocytes were placed in the M2 medium for 5 min.…”
Section: Icsimentioning
confidence: 99%
“…ICSI was performed as described previously [37]. Briefly, the haploid round sperm cell suspension was added into 1 ml M2 medium supplemented with 5 µg/ml of cytochalasin B.…”
Section: Icsi and Embryo Transfermentioning
confidence: 99%